HyOpt - Optimization-Based Development of Hybrid Materials - Triebus, Marcel; Tröster, Thomas (9th NRW Nano Conference - Innovations in Materials and Applications)

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.
Keywords: General Materials Science

Festigkeitssteigerung von Aluminiumblechformteilen der 5000-Serie durch Erweiterung der Formgebungsgrenzen stark kaltverfestigter Ausgangswerkstoffe - Camberg, Alan Adam
Leichtmetalle mit einem breiten Eigenschaftsspektrum gewährleisten die Realisierung ressourcenschonender Produkte und ermöglichen die Intensivierung sortenreiner Kreislaufwirtschaften. Die vorliegende Arbeit untersucht einen wärmeunterstützten Ansatz zur Erhöhung der Formgebungsgrenzen stark kaltverfestigter AlMg4,5 Blechwerkstoffe bei gleichzeitiger Beschränkung des Festigkeitsverlustes durch Erholungseffekte. Experimentelle Untersuchungen stellen eine wissenschaftlich fundierte Erkenntnisbasis über die werkstofftechnischen Wirkzusammenhänge des untersuchten Prozesses dar. Gepaart mit an realen Bauteilgeometrien validierten numerischen Simulationsmodellen legt diese Arbeit einen methodischen Grundstein für die industrielle Umsetzung des hier untersuchten Blechumformprozesses. Die erzielte mittlere Dehngrenze des exemplarisch untersuchten Bauteils übersteigt die Dehngrenze eines konventionellen AlMg4,5 Werkstoffes um 190 %. Mit 320 MPa entspricht sie dem Festigkeitsniveau des walzharten Blechhalbzeuges im Lieferzustand, ein Wert, der nach dem aktuellen Stand der Technik auf Bauteilebene ausschließlich mit aushärtbaren AlMgSi Legierungen darstellbar ist.
Keywords: Aluminium; Blechumformung; AlMg; Materialmodellierung; Duktiles Versagen; Halbwarmumformung; Automobil; Leichtbau; Uni-Alloy; 5000-Serie; 5182; GISSMO

Beitrag zur Reduzierung der Fehlerhäufigkeit bei der Online-Lackierung von SMC-Außenhautbauteilen - Huber, Johannes
Der Verbau von Sheet Moulding Compounds im automobilen Außenhautbereich führt in der industriellen Praxis regelmäßig zu abnehmenden Direktläuferquoten in der Technologie Oberfläche, denn neben bekannten Lackierfehlern ergeben sich auch werkstoff-spezifische Oberflächendefekte, welche einen Bauteilwechsel bedingen. Die hier vorliegende Arbeit soll einen aktiven Beitrag zur Reduzierung von Ausschuss und Nacharbeit entlang der Lackierprozesskette leisten. Zu Beginn werden die erfolgskritischen Oberflächendefekte identifiziert und die zugehörigen Fehlerursachen ermittelt, ehe anschließend die Entwicklung der Fehlstellengrößen in Folge der Temperaturbelastung während der Trocknerdurchfahrten untersucht wird. Ferner soll die Auswirkung einer zusätzlich applizierten Oberflächengrundierung auf die Fehlerhäufigkeit sowie die Oberflächengüte im decklackierten Zustand geprüft werden. Als weitere Möglichkeit zur Problemlösung wird eine in den Prozessablauf integrierte Qualitätskontrolle gesehen, weshalb in dieser Arbeit ebenso die Eignung bekannter zerstörungsfreier Prüfmethoden für die präventive Fehlererkennung überprüft und ein zweistufiges Prüfkonzept erarbeitet wird. Das Aufzeigen möglicher Handlungsalternativen sowie die kostentechnische Gegenüberstellung der verschiedenen Anbauvarianten runden die Arbeit ab.
Keywords: Sheet Moulding Compounds; SMC; Online-Lackierung

Konzeptionierung und Auslegung eines Vorderachsträgers in hybrider Leichtbauweise im C-Segment - Pöhler, Simon
Im Rahmen dieser Arbeit wurde ein neuartiger Achsträger in hybrider Bauweise entwickelt und untersucht. Dieser besteht aus einer metallischen Oberschalenstruktur und einer mit Rippen ausgeformten glasfaserverstärkten thermoplastischen Unterschale (GMT), welche zur Einstellung der optimalen Steifigkeit dient. Die Rippen und Unterschale werden hierzu in einem Fließpressverfahren entweder gemeinsam als ein Bauteil oder als separate Einzelteile hergestellt. Durch den lokalen Einsatz von Faserverbundwerkstoffen in der Unterschale und der Rippenstruktur wird ein signifikanter Gewichtsvorteil gegenüber einer Referenzstruktur aus Stahl erzielt. Durch die Verwendung des GMT-Unterbodenschutzes konnten zudem die akustischen Eigenschaften des Fahrwerks hinsichtlich der Dämpfung positiv beeinflusst werden. Die hohen Anforderungen bzgl. Steifigkeit, Festigkeit und Beständigkeit der sicherheitsrelevanten Fahrwerkskomponente konnten unter Einhaltung des Bauraums erfüllt werden. Gleichzeitig konnte das Gesamtgewicht der Komponente im Vergleich zur klassischen Referenzstruktur um 30 % reduziert werden.
Keywords: hybrider Achsträger; Leichtbau; Hybridsysteme

Load Path Transmission in Joining Elements - Steinfelder, Christian; Martin, Sven; Brosius, Alexander; Tröster, Thomas (Key Engineering Materials)
The mechanical properties of joined structures are determined considerably by the chosen joining technology. With the aim of providing a method that enables a faster and more profound decision-making in the spatial distribution of joining points during product development, a new method for the load path analysis of joining points is presented. For an exemplary car body, the load type in the joining elements, i.e. pure tensile, shear and combined tensile-shear loads, is determined using finite element analysis (FEA). Based on the evaluated loads, the resulting load paths in selected joining points are analyzed using a 2D FE-model of a clinching point. State of the art methods for load path analysis are dependent on the selected coordinate system or the existing stress state. Thus, a general statement about the load transmission path is not possible at this time. Here, a novel method for the analysis of load paths is used, which is independent of the alignment of the analyzed geometry. The basic assumption of the new load path analysis method was confirmed by using a simple specimen with a square hole in different orientations. The results presented here show a possibility to display the load transmission path invariantly. In further steps, the method will be extended for 3D analysis and the investigation of more complex assemblies. The primary goal of this methodical approach is an even load distribution over the joining elements and the component. This will provide a basis for future design approaches aimed at reducing the number of joining elements in joined structures.

Joint point loadings in car bodies – the influence of manufacturing tolerances and scatter in material properties - Martin, Sven; Tröster, Thomas (ESAFORM 2021)

Experimental investigation on lightweight potentials of fiber-metal-laminates for automotive battery cases - Stallmeister, Tim; Martin, Sven; Marten, Thorsten; Tröster, Thomas

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.

Soft-magnetic behavior of laser beam melted FeSi3 alloy with graded cross-section - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Haase, Michael; Gierse, Jan; Zimmer, Detmar; Tröster, Thomas; Schaper, Mirko (Journal of Materials Processing Technology)

Parameter- und Prozessoptimierung für den additiven Fertigungsprozess im Pulverbett am Beispiel der Legierung Ti6Al4V - Ahlers, Dominik
Die additive Fertigung mittels Laser Powderbed Fusion Verfahren (L-PBF) von Metallen wird zunehmend genutzt, um Funktionsbauteile endkonturnah zu fertigen. Die in der vor-liegenden Arbeit untersuchte Parameter- und Prozessoptimierung liefert einen Beitrag zur wirtschaftlichen Nutzung des L-PBF und zeigt, dass höhere Aufbauraten bei der ganzheit-lichen Betrachtung des Prozesses realisierbar sind. Die Parameter- und Prozessoptimierung erfordert eine Untersuchung des Einflusses der Fertigungs- und Nachbearbeitungsparameter auf das erzeugte Volumen sowie auf die Mikrostruktur und die resultierenden Materialeigenschaften. Das Ziel der vorliegenden Arbeit ist die Entwicklung einer optimierten Prozessführung mit abschließender Bewer-tung der Wirtschaftlichkeit. Mit dem entwickelten Gesamtprozess wird eine um den Faktor 1,6 höhere Aufbaurate erzielt. Des Weiteren wird die Methodik zur Erarbeitung des opti-mierten Prozessfensters beschrieben, sodass die Herangehensweise auf weitere Werk-stoffe angewendet werden kann. Die mechanischen Eigenschaften werden für den stati-schen und dynamischen Lastfall untersucht und mit der Mikrostruktur korreliert. Abschlie-ßend wird die Prozessoptimierung zur Fertigung eines Demonstrators eingesetzt und wirtschaftlich validiert. Die Ergebnisse zeigen, dass durch das hier angewendete Vorge-hen eine Prozesszeitreduktion von 22,5% und eine Kostenreduktion von 11% realisiert werden kann.
Keywords: Additive Manufacturing; SLM

Ansatz zur effizienteren Auslegung von Hybridbauteilen - Hielscher, Christian; Grenz, Julian; Camberg, Alan Adam; Wingenbach, Nils (ATZ - Automobiltechnische Zeitschrift)

Approach to More Efficient Design of Hybrid Components - Hielscher, Christian; Grenz, Julian; Camberg, Alan Adam; Wingenbach, Nils (ATZ worldwide)

Residual stress measurement in GFRP/steel hybrid components - Wu, Tao; Tinkloh, Steffen Rainer; Tröster, Thomas; Zinn, Wolfgang (Proceedings of the 4th International Conference Hybrid 2020 Materials and Structures)

A simplified method for the evaluation of the layer compression test using one 3D digital image correlation system and considering the material anisotropy by the equibiaxial Lankford parameter - Camberg, Alan Adam; Tröster, Thomas

Predicting fracture at non-isothermal forming conditions: A temperature dependent extension of the LS-DYNA GISSMO fracture indicator framework - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas

Wood-based materials as a sustainable alternative for future car body construction - Schweizer, Swetlana; Akbulut Irmak, Emine Fulya; Tröster, Thomas

A Holistic Approach to Optimization-Based Design of Hybrid Materials - Triebus, Marcel; Tröster, Thomas (Proceedings 4th International Conference Hybrid Materials & Structures)

Reduction of systematic measurement deviation in acoustic absorption measurement systems - Claes, Leander; Baumhögger, Elmar; Rüther, Torben; Gierse, Jan; Tröster, Thomas; Henning, Bernd (Fortschritte der Akustik - DAGA 2020)

Numerical investigation of the hole-drilling method applied to intrinsic manufactured metal-CFRP hybrids - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Proceedings of the 4th International Conference Hybrid 2020 Materials and Structures)